Resistive Switching Behavior of SnO₂/ZnO Heterojunction Thin Films for Non-Volatile Memory Applications - Murodov, Jamoliddin X.; Yuldashev, Shavkat U.; Arslanov, Azamat O.; Botirova, Noiba U.; Xudoyqulov, Javohir Sh.; Sharipova, Ra’no Sh.; Nusretov, Rafael A.; Nebesniy, Andrey A.; Pirimmatov, Mukhammad P. (East European Journal of Physics, 2025)
This study presents the fabrication and resistive switching (RS) performance of bilayer SnO2/ZnO thin films deposited via ultrasonic spray pyrolysis on p-type silicon substrates. The heterostructures were post-annealed at 450°C to enhance crystallinity and interfacial contact. Electrical characterization using I–V measurements revealed clear bipolar RS behavior without the need for an initial forming process. The devices exhibited a stable high resistance state (HRS) and low resistance state (LRS) across multiple cycles, with an ON/OFF ratio exceeding 10². The switching mechanism is attributed to the formation and rupture of conductive filaments likely induced by oxygen vacancies at the SnO₂/ZnO interface. Bandgap estimation using Tauc plots showed values of approximately 3.17 eV and 3.41 eV for ZnO and SnO2, respectively. These findings confirm the potential of SnO2/ZnO heterojunctions as efficient materials for next-generation non-volatile memory applications.